MARXISM AND PSYCHOLOGY: A VIGNETTE - Hayes, Grahame (PINS-Psychology in Society, 2026)
There is so much to say about Marxism and psychology, and yet a discreet silence is required on this most unpalatable of topics. Ironically, part of the reason for a super abundance of thoughts and ideas concerning Marxism and psychology, is because any discussion on this topic takes place in a context of almost complete silence with regard to these matters. Let me be blunt: there is no Marxist intellectual or political culture to talk of these days in South Africa, inside or outside of the universities. And given the shift to the centre and right in many spheres of our social, political and cultural life, many commentators would in any case applaud the "demise" of Marxism. Inside the universities the imperatives of contributing to social transformation (read neo-liberal reform), and the uncritical acceptance of globalisation prohibit any serious discussion of alternatives. Outside of the universities things are no better, even in arenas supposedly concerned with workers’ rights and lives. For example, we have a Communist Party, which seems to regard Marxist critiques of the ANC’s current anti-working class politics as a felony (cf the recently announced SACP "inquiry" of Dale McKinley’s "misdemeanours"!).